Molecular Epidemiological Screening of the Genome of the Strain Coxiella burnetii NL3262 (Netherlands, 2009) Using Formal Order Analysis - S. N. Shpynov; A. S. Gumenyuk; N. N. Pozdnichenko; A. A. Skiba (Эпидемиология и вакцинопрофилактика, 2019)
Background. More than 4,000 cases of acute disease in humans were reported during the mass Q fever outbreak in the Netherlands in 2007–2010. The Coxiella burnetii NL3262 strain was isolated during this outbreak from an aborted placenta of a goat and was studied using means of molecular biology and bioinformation techniques. Goals. Approbation of a new bioinformatics approach – formal order analysis – to study the origin of the strains that caused a massive outbreak of Q fever in the Netherlands using the C. burnetii NL3262 strain. Methodology. New tools of the formal order analysis (FOA) «Map of Genes» and «Matrix of Similarity» (available at http://foarlab. org) were used in this work to study the degree of similarity of the genome (chromosome, plasmid) of this strain with the genomes of other strains of C. burnetii. The nucleotide sequences of the chromosomes of 10 C. burnetii strains and 8 plasmids were loaded from GenBank: www.ncbi.nlm.nih.gov/genome. Results. The map of genes data showed that the chromosome of NL3262 strain significantly distanced from the chromosome of other strains by the characteristic of the average remoteness of nucleotides in the chromosome (g) that ranged from 1.448295 (for Dugway 5J108-111) to 1.448865 1.449640 (for CbRSA331). This may be due to the presence of 106 copies of the «transposase family IS110» gene associated with the growth of virulence, while in the chromosomes of other strains their number ranged only from 1 to 48. The similarity matrix showed that 84.9% of C. burnetii NL3262  chromosome components had complete (100%) homology with chromosome components of strain Z3055. The percentage of similar components ranged from 12.06 to 47.14 for chromosomes of other strains. Plasmids of the pQpH1 type of strains NL3262 and RSA 331 contained 50.0% of components with complete homology. For the same type of plasmids of strain RSA 493 and its clones, the index varied from 28.89 to 29.89%, and for plasmids of other types it was from 5.56 to 6.74%. It is shown that the chromosomes of strains NL3262  and Z3055 have the highest percentage of components with complete homology. However, by the g index, chromosomes of these strains are significantly distanced from each other, due to the large number of copies of IS110 in the chromosome of strain NL3262, which caused the formation of 21 collinear blocks. This led to a change in the properties of the Q fever outbreak strains in the Netherlands and the increase in their epidemiological significance, which caused the largest outbreak in the history of the study of this infection. Conclusions. The results of the study, obtained on the basis of the application of formal order analysis, made it possible to make an assumption about the origin of the strains of Q fever in the Netherlands in 2007–2010.  It is shown that the leading reason in the reorganization of the C. burnetii genome is the adaptation of the microorganism to a new ecological niche.